ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN PENGGUNAAN SUNTIKAN 3 BULAN DI PUSKESMAS WARA UTARA PALOPO - Sri Devi Syamsuddin; Tn. Rezki; Reskiana Azizah (Voice of Midwifery, 2017)
Depo provera containing 150 mg DMPA (depo medroxyprogesterone acetate) given every 3 months. This research use Cross sectional method. Subjects were assigned as many as 35 family planning acceptors at the Wara Utara Community Health Center.The study was conducted on June 18, 2016 by analyzing factors related to the use of 3-month injection. The variables studied are knowledge, parity and motivation factors. Data analysis in this paper using logistic regression test to see the relationship between variables. The significance limit p ≤ 0.05, IK 95%.The results obtained, based on the knowledge of the variable value of p = 0.04 is smaller than the value of α = 0.05. From the analysis can be interpreted that there is relationship between mother knowledge with 3-month injection contraception. The result of the analysis of parity variable is calculated by p value = 0,036 smaller than α = 0,05. From the analysis there is a relationship between mother parity with 3-month injection contraception. For motivation value p = 0,002 smaller than value α = 0,05 or there is relation between mother motivation with 3-month injection contraception. The most statistically significant mean variables affecting the use of 3-month injection contraception is maternal motivation. Keywords :  Acceptor, Depo provera, 3 month injection